THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) IN PRIVATELY OWNED COMPANIES - Rahdian Ihsan, Lelisari Siregar & (Jurnal IUS, 2013)
Corporate Social Responsibility (CSR) has become a global issue; however, no definition of CSR is globally accepted. In Indonesia, the concept of CSR is getting stronger, especially after being firmly mentioned in the Law Number 40 of 2007 concerning on the Limited Liability Companies and the Acts Number 25 of 2007 on Investment. In recent years, some companies have implemented the CSR, including in West Lombok. In this case, the success of local government in in improving the prosperity of the community can only be achieved if all community components take a part, including the companies operating in the region. The application of CSR in the private company in West Lombok especially the Company of legal entity (PT) is referred to the NTB Provincial Regulation Number 6 of 2012 concerning on Environment and Social Responsibility of the Company as mentioned in Article 10. The programs include community development and partnership programs for micro, small business and cooperation, and programs that are directly-related to the public. However, the application is only dominant in the program that is directly-related to the public such as grants, subsidies, social assistance. The CSR programs have not been made to support community development and partnership programs for micro, small and medium enterprises. A non-incorporated company maybe referred to the Law Number 25 article 15 of 2007 concerning Investment Keywords: CSR, Implementation, Private Companies